Contributions and Convergence in the Accounting Behavior Literature: A Bibliometric Approach - Judijanto, Loso; Iskandar, Deni (West Science Accounting and Finance, 2024)
The study of accounting behavior is critical in understanding the decision-making processes within organizations and the broader financial landscape. This research employs a bibliometric approach to analyze the contributions and convergence within the accounting behavior literature. Bibliometrics offers a systematic and quantitative method to map the intellectual structure of a field, identify influential works, and track patterns of convergence among researchers. By synthesizing data from various scholarly sources, this research aims to uncover key themes, trends, and gaps in the accounting behavior literature. Through bibliometric analysis, this study provides insights into the evolution of the field, highlights seminal works, and identifies opportunities for future research.